Prevalence of cold-related symptoms among thai chicken meat industry workers: Association with workplace temperature and thermal insulation of clothing - Chotirot Chotiphan (2020)
© 2020, National Institute of Industrial Health. All rights reserved. This study determined the association of cold-related symptoms with workplace temperature and thermal insulation of clothing among Thai chicken industry workers. Three hundred workers were interviewed regarding cold-related symptoms, which were regressed on worksite temperature and protective clothing. In total, 80% of workers reported respiratory symptoms; 23%, cardiac symptoms; 62%, circulation disturbances; 42%, thirst; 56%, drying of the mouth; and 82%, degradation of their performance. When adjusted for personal characteristics, respiratory symptoms were 1.1‒2.2 times more prevalent at −22‒10°C than at 10‒23°C. At −22‒10°C, cardiac symptoms increased by 45%, chest pain by 91%, peripheral circulation disturbances by 25%, and drying of the mouth by 57%. Wearing protective clothing with at least 1.1 clo units was associated with marked reductions in symptom prevalence. Therefore, temperatures lower than 10°C increased prevalence of cold-related symptoms, which are largely preventable by appropriate clothing use.